SAT0549 Validation of 3 Novel Autoantigens for Systemic Sclerosis. (15th July 2016) - Schulte-Pelkum, J.; Budde, P.; Zucht, H.D.; Wirtz, D.; Schulz-Knappe, P.; Distler, O.; Jordan, S.; Hunzelmann, N.; Schneider, M.; Maurer, B.
Abstract : Background: Systemic sclerosis (SSc) is a systemic autoimmune disease that manifests as progressive fibrosis of the skin and internal organs. SSc is associated with the presence of several autoantibodies (aab) to intracellular targets, with the three most important SSc-specific being anti-centromere antibodies, anti-Scl70 antibodies and anti-RNA polymerase III antibodies, which occur in over 50% of SSc patients. Autoantibody specificities are strongly associated with pattern of organ involvement and disease outcome, making autoantibodies an essential tool in the clinical management of SSc. This highlights the need for additional specific and sensitive diagnostic and prognostic biomarkers in SSc. We have recently conducted high-content autoantibody profiling studies of SSc, systemic autoimmune diseases (AID), and healthy controls and found novel SSc associated autoantibodies. Objectives: These novel SSc-associated autoantibody biomarker candidates and their diagnostic value were evaluated by testing samples derived from different SSc cohorts from the University Hospital Düsseldorf and the University Hospital Zurich. Methods: Three novel identified biomarker candidates, namely Lysine (K)-specific demethylase 6B ( KDM6B ), Protein Phosphatase Inhibitor 2 (PPP1R2) and Bicaudal Drosophila Homolog 2 (BICD2) were developed into ELISA Kits using highly purified recombinant antigen and evaluated. Autoantibody specificities were analyzed using an independent and well characterized cohort consisting with sera of patients suffering from SSc (n=198), myositis (n=20), RA (n=20), SLE (n=40) and healthy blood donors (n=132). Assay threshold levels were calculated using a receiver operation characteristic analysis and set for specificities of >95%. Results: Using the respective cut-off for the ELISA tests we were able to find autoantibody reactivity against BICD2 in 29.2% of SSc patients and 4.8% of control samples, against PPP1R2 in 15% SSc and 3.2% of controls and against KDM6B in 20% of SSc patients and 2.6% of control samples, respectively. Positive results of anti-BICD2 and anti-PPP1R2 aab co-migrated with anti-Centromere aab, but were also found in anti-Centromere and anti-Scl-70 negative samples. Interestingly, both anti- BICD2 and anti-PPP1R2 aab were found in SSc samples tested negative for anti-RNA Polymerase III auto-reactivity. Conclusions: In this study we were able to confirm the diagnostic value and high specificity of the newly discovered autoantigens using ELISA. Anti-BICD2 aab showed significant inverse correlation with pulmonary fibrosis. Thus, anti-BICD2 aab may be associated with a decreased incidence of severe lung disease. Disclosure of Interest: J. Schulte-Pelkum Employee of: Protagen AG, P. Budde Employee of: Protagen AG, H. Zucht Employee of: Protagen AG, D. Wirtz Employee of: Protagen AG, P. Schulz-Knappe Employee of: Protagen AG, O. Distler Grant/research support from: Bayer, Sanofi, Ergonex, Boehringer Ingelheim, Actelion, Pfizer, Consultant for: 4 D Science, Actelion, Active Biotec, Bayer, BiogenIdec, BMS, Boehringer Ingelheim, EpiPharm, Ergonex, espeRare foundation, Genentech/Roche, GSK, Inventiva, Lilly, medac, MedImmune, Pharmacyclics, Pfizer, Serodapharm, Sinoxa, S. Jordan: None declared, N. Hunzelmann: None declared, M. Schneider: None declared, B. Maurer: None declared